Survey of Ehlers‒Danlos Patients' ophthalmic surgery experiences. Issue 4 (27th January 2020) - Louie, Anita; Meyerle, Catherine; Francomano, Clair; Srikumaran, Divya; Merali, Farhan; Doyle, Jefferson J.; Bower, Kraig; Bloom, Lara; Boland, Michael V.; Mahoney, Nicholas; Daoud, Yassine; Singman, Eric L.
Abstract: Background: Ehlers‒Danlos Syndrome (EDS) is a rare disease affecting approximately 1 in 5, 000 people. Although ophthalmic conditions associated with EDS have been described, little data exist concerning ophthalmic surgical outcomes experienced by EDS patients. Methods: Patients with EDS were surveyed via the EDS Society and asked about their ophthalmic surgical experiences including procedure, complications, and the timing with respect to receiving the EDS diagnosis. Complications were confirmed as such by subspecialists. Results: Of 579 respondents, 467 reported confirmed EDS, and 112 of those had an ophthalmic procedure, including refractive surgery, cataract/lens surgery, retinal surgery, strabismus surgery, oculoplastic surgery, corneal surgery, and laser surgery for glaucoma. The rate of confirmed complications was: 23%‐refractive, 33%‐lens/cataract, 33%‐retina, 59%‐strabismus, 23%‐ oculoplastics, 0%‐cornea, and 25%‐glaucoma laser. In addition, 76% of patients underwent surgery prior to the EDS diagnosis. Conclusions: Patients with EDS may have elevated risk of postoperative ophthalmic surgical complications. It would seem reasonable to systemically and prospectively explore how patients with EDS respond to ophthalmic surgery. Furthermore, it would seem circumspect to ask surgical candidates patients about whether they carry a diagnosis of EDS or have signs and symptoms of EDS prior to surgery. Abstract : Eye surgery on patients with Ehlers‒Danlos may have a higher complication rate than seen in the general population. Surgeons should be cognizant that the diagnosis of Ehlers‒Danlos might not be made in patients suffering this condition.